2014
DOI: 10.1213/ane.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Universal Intravenous Access Cleaning Device Fails to Sterilize Stopcocks

Abstract: These data suggest that when the inner surface of the COLD is contaminated, both alcohol pads and Site-Scrub were not significantly effective in decontaminating the COLD. When the COLD rim is contaminated, however, alcohol pads outperform Site-Scrub. DNCCs were uniformly decontaminated with either treatment. Future work should focus on better access systems because current COLDs are difficult to decontaminate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…These studies suggest that while both open and closed lumen intravascular devices can be disinfected, DNCCs are more easily decontaminated. Future work should more extensively compare the efficacy of different hub disinfection systems in reducing contamination of DNCCs in the clinical environment [19].…”
Section: Key Pointsmentioning
confidence: 99%
“…These studies suggest that while both open and closed lumen intravascular devices can be disinfected, DNCCs are more easily decontaminated. Future work should more extensively compare the efficacy of different hub disinfection systems in reducing contamination of DNCCs in the clinical environment [19].…”
Section: Key Pointsmentioning
confidence: 99%
“…The Holroyd in vitro study at University of Florida compared the single use of this cleansing cap with 70% alcohol to traditional 70% alcohol wipes [151]. When the cleansing cap was used on stopcocks Holroyd found contamination and increased CFU.…”
Section: Passive Disinfectionmentioning
confidence: 99%
“…When the cleansing cap was used on stopcocks Holroyd found contamination and increased CFU. This study found 70% alcohol wipes and this alcohol cleansing cap were both effective on the surface of NC and catheter hubs [151]. Other groups also used this single use cleansing cap in combination with other 70% alcohol disinfecting caps designed to be left in place until the next access [14,177].…”
Section: Passive Disinfectionmentioning
confidence: 99%
“…For diseases with high fatality rates that lack specific and effective treatment, it is prudent to take a more extreme prevention strategy than that based on the documented transmission route. 2 One example in which this strategy is applied is Ebola virus disease, for which extreme precautions are taken. 3 Given that SFTS virus (SFTSV) is a viral hemorrhagic fever virus that causes severe disease with a high fatality rate, we apply the same strategy to SFTS.…”
mentioning
confidence: 99%
“…To date, airborne transmission of naturally occurring hemorrhagic fever viruses has not been documented. 2 The patient in the Moon et al article was a doctor wearing only a fluid-shield mask and gloves who performed endotracheal intubation on an SFTS patient and was infected with SFTS thereafter. Respiratory droplets are thought to be generated during endotracheal intubation, and protection of the eyes, nose, and mouth is recommended during the procedure in accordance with standard precautions.…”
mentioning
confidence: 99%